SEMIOTIKA KEHIDUPAN MASYARAKAT MODERN DALAM VIDEO CHAINED TO THE RHYTHM - Renny Candradewi Puspitarini (President University, 2018)
Abstract. The articles argues that the post-modern life in current state can be explored some more by studying what songs are played within the years. In 2017, Katy Perry’s Chained to The Rhythm becomes hit record-breaking not only for its lyrics and video but also for its intriguing feature since meanings never just textual. They are also sociopolitical and it is upon this dimension semiology prevails. The writing employs method of semiotic with semiotic analysis that can help understand what norms are being deviated from, to what extent, and possibly, to what effect. Combined with literature study, the article finds visual metaphor exist predominantly side by side with the lyrics during the video played in the background to insert and superimpose objects in one syntagma into another. Both lyrics and video played in Katy Perry’s Chained to the Ryhthm is completed by a unit from the paradigm of the post-modern life characteristics.Keywords: Media Ecology Theory, Semiotic Analysis, Social message, communication from video, Post-modern